A recombinant adenovirus vector containing the synNotch receptor gene for the treatment of triple-negative breast cancer - A, Ruhan; Kunimura, Naoto; Tominaga, Shoko; Hirata, Erika; Nishioka, Shunya; Uesugi, Misato; Yamazaki, Rion; Ueki, Hideto; Kitagawa, Koichi; Fujisawa, Masato; Shirakawa, Toshiro (Frontiers in Oncology, 2023)
Triple-negative breast cancer (TNBC) is known as the most difficult molecular subtype of breast cancer to treat. Recent studies revealed that cancer stem cells (CSCs) play a critical role in TNBC recurrence and metastasis. In this study, we developed a recombinant replication-deficient adenoviral vector (Ad-CD44-N-HIF-3α4), which contains a gene encoding a synthetic Notch (synNotch) receptor composed of the extracellular domain of CD44 (CD44-ECD) and the hypoxia-inducible factor (HIF)-3α4 connected by the Notch core regulatory region. CD44 is a transmembrane glycoprotein and known as a CSC marker in breast cancer and other malignancies. HIF-3α4 is a dominant-negative regulator of HIF-1α and HIF-2α and inhibits hypoxia-inducing effect. Both CD44 and HIF signals contribute cancer stemness and maintaining CSCs in breast cancer. The CD44-ECD in the synNotch receptor acts as the CD44 decoy receptor, and after a ligand such as a hyaluronic acid binds to the CD44-ECD, HIF-3α4 is released from the Notch core domain. We performed an in vivo study using a mouse xenograft model of MDA-MB-231, a highly invasive TNBC cell, and confirmed the significant antitumor activity of the intratumoral injections of Ad-CD44-N-HIF3α4. Our findings in this study warrant the further development of Ad-CD44-N-HIF3α4 for the treatment of patients with TNBC.